Estimation of the Effects of Estradiol Hormone ‎Concentrations on the Activities of Some ‎Clotting Factors (FI, FII, VII,VIII, IX) Involved in ‎Extrinsic, Intrinsic, and Common Pathways ‎During Pregnancy (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study was conducted to confirm the effects and correlations  of estradiol hormone  on  some major clotting factors (fibrinogen FI , prothrombin FII,  stable factor F VII,  antihemophilic factor FVIII,  and chrismas factor IX) during pregnancy phases.  Seventy five (75) pregnant women at different stages of pregnancy and were sub- divided into third groups according to period of  gestational phases , included twenty five (25) pregnant women in each group (first, second, third trimesters). Twenty (20) volunteer  non-pregnant non-lactating women were involved in this study and used as a control group. All ages of tested  women ( pregnant and non- pregnant) were between 25 year  to 35 year old . Regarding levels of estradiol hormone , they were showed insignificant elevation (p>0.05) during first trimester and remarkable increase (p< 0.05) during second and third trimesters when matched with their counterparts of non- pregnant group. About concentrations of fibrinogen factor (FI) , they were indicated a significant heightening (p< 0.05) during all phases of pregnancy in matching with control group, and these concentrations have a positive correlation (r =0.714) with levels of estradiol.  Activities of prothrombin factor ( F II) were significantly elevated (p 0.05 ) in first and second trimesters and its activities become increased (p< 0.05) at third trimester in a comparison with those of control group, and pointed out a significant positive correlation ( r = 0.412 ) with estradiol level  .   Estimation of intrinsic pathway activities (antihemophlic factor FVIII and Chrismas factor FIX ) were showed a progressive elevation  (p< 0.05) during first, second, and third trimesters in a comparison with control group, and these activities confirmed a significant positive correlation  (r =0.260 , r =0.632, respectively) with estradiol.